(untitled) (Indonesian Court and Justice Review, 2025)
The 2024 Presidential Election in Indonesia has positioned the Constitutional Court as a pivotal institution in safeguarding electoral integrity. Historically tasked with resolving electoral disputes, the Court’s expanded involvement in pre-election processes, including candidate eligibility and the interpretation of constitutional requirements, has raised critical questions about its neutrality, legitimacy, and institutional boundaries. This study analyzes the evolving role of the Constitutional Court in the 2024 electoral context, particularly its controversial ruling on age requirements for presidential and vice-presidential candidates. Employing a legal-political analysis, this research examines court decisions, political discourse, and media framing to understand how judicial interpretations affect public trust and the democratic process. The findings suggest a shift in the Court’s function—from a post-election arbiter to a proactive political actor—creating tensions between legal reasoning and perceived political alignment. While some decisions have contributed to legal clarity, others have sparked accusations of partisanship and judicial activism. The study highlights the broader implications of this trend for the separation of powers, rule of law, and democratic consolidation in Indonesia. The novelty lies in its timely analysis of the 2024 election as a legal stress test for the Court’s institutional credibility. It offers recommendations to reinforce judicial independence and electoral accountability in future cycles.